Latihan Aerobic Exercise terhadap Kadar Glukosa Darah pada Penderita Diabetes Mellitus Tipe 2 - Geladis Titanik; Andri Setiya Wahyudi; Ika Nur Pratiwi (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the effect of aerobic exercise on blood glucose levels in patients with type 2 diabetes mellitus. The research method used quantitative research with a quasi-experimental design with a pretest-posttest approach in the aerobic exercise group and the control group by measuring blood glucose levels including fasting blood glucose tests using a glucometer. The study showed that fasting blood glucose decreased on average from 155 ± 9.41 mg/dL to 144 ± 9.31 mg/dL (p < 0.001), with a range from 139–167 mg/dL to 127–155 mg/dL. These results indicate that aerobic exercise interventions can significantly lower blood glucose levels. Aerobic exercise has been shown to be effective in improving glycemic control and metabolic health in individuals with type 2 diabetes mellitus (T2DM). In conclusion, there is a significant effect of aerobic exercise on blood sugar levels in T2DM patients. Aerobic exercise significantly reduces fasting blood glucose levels in patients with Type 2 Diabetes Mellitus.  Keywords: Aerobic Exercise, Diabetes Mellitus, Blood Glucose Levels